Designing a new Vaccine Based on Multiple Epitopes Against Monkeypox Virus with the help of new Methods Based on Immunoinformatics Software: Designing a new Vaccine Based on Multiple Epitopes Against Monkeypox Virus by Immunoinformatics Software - Saeed Pirmoradi (Iranian Journal of Pharmaceutical Sciences, 2022)
Monkeypox virus is a zoonotic virus belonging to the family of Poxviridae and the genus Orthopoxvirus, which is the cause of a viral disease between humans and animals, the characteristics of which are comparable to other cases of smallpox with some differences. Recently some patients caused by the monkeypox virus (MPXV) were reported to the WHO. In recent years, the widespread and rapid spread of some epidemics highlighted the need for the rapid development of effective vaccines in scientific communities. Although conventional therapies have played an essential role in the treatment of many diseases, emerging diseases require new methods of treatment with fewer complications. It is therefore important to develop an effective vaccine for infections caused by the Monkeypox virus to prevent mortality and the safety of the community. In this research, we have used bioinformatics to design a vaccine against the F13 envelope protein Monkeypox virus. A total epitope confined to B cells and MHC I and II alleles were structurally constructed in F13 envelope protein to stimulate immunity and antibody recognition which was used to construct a chimeric peptide vaccine. The vaccine was predicted as a stable, antigenic, and non-allergenic combination. analysis of the TRL4/vaccine docking complex and simulation indicate a sufficiently stable binding with receptor activation. The immune response simulation following hypothetical immunization indicates the potential for stimulation and production of active and memory B cells, as well as the potential for cell production of CD8 + T, CD4 + T, and the development of effective immunological responses induced by Th2 and Th1. Analysis of the in silico processes have shown that the structure of the vaccine produces high antigenicity and good cellular immunity in the host body and stimulates various immune receptors such as TLR4, MHC I and MHC II. Vaccine function was also associated with increased IgM and IgG and a set of Th1 and Th2 cytokines. But final confirmation of the effectiveness of the designed vaccine requires clinical processes.